2016
DOI: 10.1177/0884533616639401
|View full text |Cite
|
Sign up to set email alerts
|

Does Bedside Sonography Effectively Identify Nasogastric Tube Placements in Pediatric Critical Care Patients?

Abstract: Bedside sonography performed by a radiologist is an effective and sensitive diagnostic procedure for confirming the correct NGT position in patients in the pediatric critical care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 28 publications
(80 reference statements)
0
36
0
Order By: Relevance
“…The efficacy and sensitivity of BUSG in verifying gastric tube location has been reported in both adult and pediatric ICU patients. [ 14 15 16 33 ] Despite its efficacy, the routine use of ultrasonography requires additional equipment, which may delay the process when the equipment is located outside of the intensive care unit. However, as BUSG has seen increased use in the ICU setting for several indications, routine availability of equipment is being more common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy and sensitivity of BUSG in verifying gastric tube location has been reported in both adult and pediatric ICU patients. [ 14 15 16 33 ] Despite its efficacy, the routine use of ultrasonography requires additional equipment, which may delay the process when the equipment is located outside of the intensive care unit. However, as BUSG has seen increased use in the ICU setting for several indications, routine availability of equipment is being more common.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 15 ] We have previously shown that bedside ultrasonography (BUSG) can confirm NOGT location in patients in the pediatric intensive care unit when performed by a radiologist. [ 16 ] The current study prospectively evaluates the efficacy of BUSG when determining NOGT location in neonates. Since it is not always feasible to consult a radiologist to perform BUSG for the verification of the NOGT location, we also investigated whether a critical care physician could perform BUSG.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasound technology as a noninvasive substitute for radiologic imaging to verify NGT placement shows promise. A recent study in a pediatric intensive care unit demonstrated 100% sensitivity with the use of ultrasound for correct placement of NGTs at the bedside when operated by a radiologist . Further investigation into the feasibility and applicability of ultrasound to verify NGT location in children at the bedside by nonradiologists is needed.…”
Section: Current Practicementioning
confidence: 99%
“…A recent report from Turkey looked at the use of ultrasound to verify NG tube placement in critically ill children 19 . This concept is intriguing because it is noninvasive and similar to procedures used in percutaneous intravenous (IV) central catheter placement.…”
Section: Temporary Enteral Access Devicesmentioning
confidence: 99%